ANALISIS KINERJA BADAN KEPEGAWAIAN DAERAH KOTA SEMARANG - Sigit Pramugi; Nina Widowati; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This study aims to describe the performance of the Agency's Staffing area of Semarang and to know what aspects of the lead Agency staffing performance area ofSemarang is not optimal. Locus were used in this research is the staffing agency's Regional Office in the city of Semarang. This research uses qualitative research methods are purely descriptive. The subjects in this study consists of five main informant.Based on the research results show that the performance of the staffing Agency's Office in Semarang City Area can be categorized Either even though there is still some dimensions assessed less well. Aspects that affect optimal performance of Regional Staffing Agency Semarang which aspects of competence and motivation aspects.Conclusions in this study was the overall performance of the civil service agency of The city of Semarang was good, and the aspect of the competence and motivation indeedaffect Staffing Agency performance Area of Semarang. Based on the conclusions researchers recommended to a local employee of semarang to fix dimensions still was not well that more optimal performance can be achieved.